The Todaro paradox revisited - Yves Zenou (Institute for the Study of Labor (IZA), 2005)
The Todaro Paradox states that policies aimed at reducing urban unemployment are bound to backfire: they will raise rather than reduce urban unemployment. The aim of this paper is to reexamine this paradox in the context of efficiency wage and search-matching models. For that, we study a policy that consists in decreasing the urban unemployment benefit. In an efficiency wage model, we find that there is no Todaro paradox while this is not always true in a search-matching model since a decrease in the urban unemployment benefit can increase both urban employment and unemployment.
Keywords: D83; J41; J64; O15; 330; efficiency wages; search-matching; rural-urban migration; policy